THE IMAGE OF WOMEN IN WILLIAM SOMERSET MAUGHAM’S SHORT STORIES = HÌNH ẢNH NGƯỜI PHỤ NỮ TRONG TRUYỆN NGẮN CỦA WILLIAM SOMMERSET MAUGHAM - Nguyễn, Mỹ Linh (2020)
As an attempt to contribute to gaining more insights into Maugham’s works, this research aims to investigate the portrayal of women at the early twentieth century depicted in his short stories. Specifically, the study focuses on both similar and different characteristics amongst the female characters in the five short stories. They have three main similar characteristics including selfishness, hypocrisy and adultery. Besides, the attitude of the writer, Maugham on these characters is also analyzed based on moral aspects and humanistic viewpoints.